Effects of Information Load on Schema and Episodic Memory Formation - Harkotte, Maximilian; Contreras, María P.; Inostroza, Marion; Born, Jan (Frontiers in Behavioral Neuroscience, 2022)
The formation of semantic memories is assumed to result from the abstraction of general, schema-like knowledge across multiple experiences, while at the same time, episodic details from individual experiences are forgotten. Against this backdrop, our study examined the effects of information load (high vs. low) during encoding on the formation of episodic and schema memory using an elaborated version of an object-place recognition task in rats. The task allowed to abstract a spatial rule across 4 (low information load) or 8 (high information load) encoding episodes (spaced apart by a 20 min interval) in which the rats could freely explore two objects in an open field arena. After this encoding phase, animals were left undisturbed for 24 hours and then tested either for the expression of schema memory, i.e., for the spatial rule, or memory for an individual encoding episode. Rats in the high information load condition exhibited a more robust schema memory for the spatial rule than in the low information load condition. In contrast, rats in the low load condition showed more robust memory for individual learning episodes than in the high information load condition. Our findings of opposing effects might point to an information-load dependent competitive relationship between processes of schema and episodic memory formation, although other explanations are possible.